2016
DOI: 10.1080/10245332.2015.1122259
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcome and healthcare costs of relapsed or refractory multiple myeloma: A retrospective analysis from the Chinese experience

Abstract: Real-world costs during treatment of RRMM varied greatly. Total costs during bortezomib-based regimens are significantly higher compared with non-bortezomib regimens. Further multi-center studies are needed to assess the cost-effectiveness of bortezomib for the treatment of RRMM in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These guidelines predominantly advocate for proteasome inhibitor-based therapies, as they offer superior response rates and improved survival outcomes, alongside the use of thalidomide, melphalan, lenalidomide, and cyclophosphamide [14]. In comparison to cost estimates from other countries, the monthly cost per patient for therapy medications alone in Singapore is higher than those reported in China [15], The Netherlands [16], and Germany [17], but considerably lower than the costs in the United States [18,19], which are nearly double. Several factors contribute to these variations.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines predominantly advocate for proteasome inhibitor-based therapies, as they offer superior response rates and improved survival outcomes, alongside the use of thalidomide, melphalan, lenalidomide, and cyclophosphamide [14]. In comparison to cost estimates from other countries, the monthly cost per patient for therapy medications alone in Singapore is higher than those reported in China [15], The Netherlands [16], and Germany [17], but considerably lower than the costs in the United States [18,19], which are nearly double. Several factors contribute to these variations.…”
Section: Discussionmentioning
confidence: 99%
“…Several large studies examining the real-world costs of multiple myeloma in the US and China have been published in the last few years 6,8,9 , but recent European data (since 2013) reporting costs associated with novel agents are lacking. In particular, the relatively recent availability of pomalidomide and bendamustine has not been captured in the few published European studies [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates, we screened 226 records and assessed 138 full-text articles based on inclusion and exclusion criteria. Eventually, 92 pharmacoeconomic evaluations were included in the review and underwent data extraction (figure 1), detailed information on included studies can be found in online supplemental table 2 19–110…”
Section: Resultsmentioning
confidence: 99%